L’intervention développementale comme outil d’expansion de l’activité d’animation d’ateliers de slam de poésie - Élodie Géas; Vincent Grosstephan; Stéphane Brau-Antony (Recherches en Éducation)
Developmental interventions represent an alternative form of research that is resolutely activist and interventionist, supporting the efforts of actors to reconceptualize and transform their activity, thus questioning their respective places. The case study presented here analyzes the development of the poetry slam workshop facilitation activity, co-facilitated by a teacher and an artist-slammer. The actors of this animation activity, teachers, slammers but also students, are directly involved in the research device, inspired by the change laboratory. The methodology used ex-periments with the possibilities of development of the activity that can be aroused by the researcher, especially thanks to the identification by the practitioners of a shared object, resulting in an evolution of the division of labor. Thus, the respective positions of researchers and professionals in the research process are evolving, which favors the reappropriation by practitioners of their activity and individual and collective emancipation.